THE CHARACTERISTICS OF ENGLISH CARETAKER SPEECH FOUND IN IMAGINE THAT MOVIE - Pambudi, Dewi Sri (Universitas Muhammadiyah Surakarta, 2015)
This research aims at describing the types of language forms and functions found in Imagine That movie. The type of this research is descriptive qualitative. The objects of the research are utterances by adults addressed to children. Subjects of this research are the caretakers found in Imagine That movie, covering father and mother. The writer used the manuscript of conversation Imagine That film as data source. The data were collected through documentation technique with the following steps: watching the original film and reading the movie script, underlining the caretaker utterances then writing them down. The data were analyzed qualitatively. The results show there four types of word: noun, verb, adjective, and adverb and four types of phrase: noun phrase, verb phrase, adjective phrase, and adverbial phrase and four types of sentence: declarative sentence, interrogative sentences, exclamatory sentences, and imperative sentences. With regards to language function, there are seven kinds: instrumental function, interactional function, regulatory function, imaginative function, personal function, representational function, and heuristic function.